Maintenance Rituximab after high-dose therapy and autologous stem cell transplantation in mantle cell lymphoma - Roider, Tobias; Dietrich, Sascha (Biology of blood and marrow transplantation, 2017)
Abstract: Mantle cell lymphoma (MCL) is an aggressive B cell lymphoma characterized by early dissemination and an unfavorable clinical course. Treatment with conventional chemotherapy resulted in unsatisfactory outcomes and a median survival of less than 3 years after diagnosis of MCL [1]. In recent years, the prognosis of patients with MCL has improved considerably, and the refinement of dose-intensified approaches such as autologous stem-cell transplantation (ASCT) has contributed significantly to this development.
Gesehen am 10.04.2018